Lost in Translation? A Comparative Analysis of Love and Emotion in Yvain ou Le Chevalier au Lion and Ívens saga - Teeter, Kathryn, 1991- (2020)
While medieval French romances are full of emotive language and detailed descriptions expressly addressing character’s emotional states, Old Norse and Old Norse-Icelandic texts are considered to be lacking in comparison. This view is incorrect, as there is plenty of emotion waiting to be inferred just beneath the surface. The purpose of this thesis is to examine the different definitions and purposes of love and the emotional responses attached to it in two different medieval emotional communities: twelfth century feudal France, and thirteenth and fourteenth century Norway and Iceland. It also aims to show that emotional language and the approach to the different types of love under discussion are influenced in the following ways: French feudal society is occupied by concerns with political, courtly, and religious aspects of life while Norway and Iceland are occupied by honour, a very different, but equally important, aspect of their society. By analysing the textual differences in Chrétien de Troyes’ Yvain ou le Chevalier au Lion and the Old Norse-Icelandic translation, Ívens saga, we can see how various social and cultural differences between the two communities shape the way that their audiences understand and value love and emotion, and how this affects character dialogue and interaction. Riddarasögur like Ívens saga provided a unique look at the cultural and emotional landscape of medieval Scandinavia. They contain less expressly stated emotion than their French counterparts, but show much more than traditional genres like the Íslendingasögur. The influences identified in this research suggest that medieval French texts held a preference for passionate, lengthy passages relating to love and emotional expression. Old-Norse Icelandic influences suggest a preference for action over emotion, with love and emotion being worked into the story in a way that compliments the heroic values that were of central importance to the Nordic communities. Í samanburði við franskar riddarasögur, sem inniheldur ...